Cinética de deterioro de vitamina C, capacidad antioxidante y acidez de zumo de pitahaya amarilla (Hylocereus megacanthus) - Sumaran Contreras, Heison Apolonio (2019)
The main objective of this research work was to evaluate the effect of storage temperature on the kinetics of vitamin C, antioxidant capacity and acidity of yellow pitahaya juice (Hylocereus megacanthus) packaged in low density polyethylene bags. For this, the juice of the pitahaya was obtained and stored at temperatures of 5, 25 and 40 °C for a period of 15 days. The physicochemical parameters were determined every 24 hours. The results obtained indicate that both the content of vitamin C, antioxidant capacity and acidity decrease over time, being greater as the temperature increases. Experimental data indicate a trend with zero order kinetics for antioxidant capacity and second order for vitamin C content and acidity of pitahaya juice. The velocity constant values (k) calculated for each parameter indicate that they are higher when the storage temperature is higher. Regarding the activation energy, this was higher for acidity (20.47 ± 0.63 kJ/mol) followed by vitamin C (16.31 ± 0.27 kJ/mol) and antioxidant capacity (12.19 ± 0.49 kJ/mol). The analysis of variance demonstrates a high dependence (p < 0.05) of the deterioration kinetics with the storage temperature, in addition to a statistically significant difference for each parameter depending on the temperature.